THE ROLE OF GRAPHIC DESIGN IN ENHANCING AI TECHNOLOGY ACCEPTANCE AS A MEDIATOR FOR UTILIZATION BY BUSINESS GROUPS OF CHILDREN WITH DISABILITIES - Eko Fikriando; Muhamad Ilham; Ramadhi Ramadhi; Hanafi Malik; Juwita Wirta Sri Depi; Heru Pranata; Ifdal Irman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the role of inclusive graphic design in enhancing the acceptance and utilization of artificial intelligence (AI) technologies among children with disabilities. Using a quantitative approach, data were collected from 97 respondents within the Adisa business group, employing a structured questionnaire to measure graphic design quality, AI acceptance, and utilization. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze the relationships between these variables. The findings reveal that graphic design significantly influences both the acceptance and utilization of AI technology, with user acceptance mediating this relationship. These results highlight the importance of user-centered and inclusive design in reducing barriers to AI adoption and ensuring equitable access for marginalized populations. By extending the Technology Acceptance Model to include inclusivity as a critical factor, this study contributes to the theoretical understanding of technology adoption while providing actionable insights for developers, businesses, and policymakers. The implications underscore the need for culturally sensitive and cost-effective design practices to foster widespread adoption and utilization of AI technologies. Future research is encouraged to explore the intersection of design, functionality, and socio-economic factors to further advance inclusive technological innovation.